2019
DOI: 10.21839/jaar.2019.v4i1.262
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis, proximate composition and antibacterial activities of Ziziphus Species (Z. jujube and Z. spina christi)

Abstract: Despite tremendous progress in human medicines infectious diseases caused by bacteria, fungi, viruses and parasites are still a major threat to public health. Their impact is particularly large in developing countries due to relative unavailability of medicines and emergence of widespread drugs resistance.The aim and objectives of this research work was designed to carried outthe Phytochemical analysis, proximate composition and to evaluate the antimicrobial activities of the Ziziphus jujube and Ziziphus spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
1
9
1
Order By: Relevance
“…Based on these data, it seems likely that Sidr extract is potentially a natural antibiotic in aquaculture. The results in this study are in line with those of Alhassan et al (2019), Al-Mutairi et al (2016, Khaleel et al (2019), andTemerk et al (2017). The results indicate that the Sidr leaf extract has the potential as an antibacterial agent.…”
Section: Inhibition Test Of Sidr Leaf Extract Against Several Aquaculture Pathogenic Bacteriasupporting
confidence: 92%
See 1 more Smart Citation
“…Based on these data, it seems likely that Sidr extract is potentially a natural antibiotic in aquaculture. The results in this study are in line with those of Alhassan et al (2019), Al-Mutairi et al (2016, Khaleel et al (2019), andTemerk et al (2017). The results indicate that the Sidr leaf extract has the potential as an antibacterial agent.…”
Section: Inhibition Test Of Sidr Leaf Extract Against Several Aquaculture Pathogenic Bacteriasupporting
confidence: 92%
“…Different results are shown byIbrahim et al (2015), who found alkaloids to be the significant phytochemical of Sidr leaf from Nigeria Ermias et al (2011). andAlhassan et al (2019) found that steroid, flavonoid, tannin, lipid, anthraquinone, saponin, and alkaloid are present in Z. spina-christi leaf extracts. By contrast,Suliman and Mohammed (2018) found that the phytochemical components of Sidr leaf from Sudan do not contain steroids.…”
mentioning
confidence: 97%
“…Beavo and Brunton (2002) found that jujube fruits contain a certain amount of cAMP, which has a positive e ect on the heart muscle, nutritional myocardium and diastolic blood vessels, as well as having anti-arrhythmia and anti-platelet aggregation e ects. Recent phytochemical research on jujube fruits has revealed anti-cancer, anti-in ammatory, anti-obesity, immuno-stimulating, anti-oxidant, hepato-protective and gastro-intestinal protective properties, as well as inhibition of foam cell formation in macrophages (Abedini et al, 2016;Keerthi et al, 2016;Rajopadhye, Upadhye, 2016;Alhassan et al, 2019). Cosmulescu et al (2017) mentioned that jujube fruits are rich in bioactive compounds ( avonoids, carotenoids and anthocyanin) and can complement a healthy human diet.…”
Section: Traditional Medicinal Uses and Potential Health Benefits Of mentioning
confidence: 99%
“…has not yet been investigated extensively, although reports have shown that Z. spina-christi was potentially a good source of antimicrobial compounds and other functional groups. The Ziziphus genus has previously been found to include a variety of functional substances including vitamin C, amino acids, triterpene acids, polysaccharides, polyphenols, flavonoids, triterpene acids, saponins, alkaloids, indole derivatives, and fatty acids [ 6 ]. The use of these compounds especially for applications in crop protection was not as common as in the medical field [ 7 ].…”
Section: Introductionmentioning
confidence: 99%